2013
DOI: 10.1155/2013/315365
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Promoter Polymorphism IL-6 −174G/C in Dermatomyositis and Systemic Lupus Erythematosus

Abstract: The promoter polymorphism −174G/C within the interleukin-6 gene (IL-6) has been reported to have a functional importance through the modulation of IL-6 gene expression in vitro and in vivo. IL-6 is thought to play an important role in autoimmune diseases and the effect of its receptor inhibitor—tocilizumab—has been recently studied. The aim of this case-control study was to investigate the association between the interleukin-6 −174G/C single nucleotide polymorphism and the susceptibility to dermatomyositis (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Six studies in all investigated the association of the IL-6-174 G/C polymorphism with clinical and laboratory characteristics (malar rash, discoid skin lesions, photosensitivity, oral ulcer, arthritis, serositis, nephritis, neurological disorder, haematological disorder, haematological compromise, central nervous system disease, thrombocytopenia, anti-double stranded (ds)DNA, anti-Ro, anti-La, anti-Sm, anti-histones, anticardiolipin and anti-β 2 -glycoprotein antibodies). 13,1923 The results of association between this polymorphism and discoid skin lesions or renal disease remain controversial, while other association was not statistically significant in these six studies. Therefore, a meta-analysis was carried out to evaluate the association of the IL-6-174 G/C polymorphism with discoid skin lesions and renal disease.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Six studies in all investigated the association of the IL-6-174 G/C polymorphism with clinical and laboratory characteristics (malar rash, discoid skin lesions, photosensitivity, oral ulcer, arthritis, serositis, nephritis, neurological disorder, haematological disorder, haematological compromise, central nervous system disease, thrombocytopenia, anti-double stranded (ds)DNA, anti-Ro, anti-La, anti-Sm, anti-histones, anticardiolipin and anti-β 2 -glycoprotein antibodies). 13,1923 The results of association between this polymorphism and discoid skin lesions or renal disease remain controversial, while other association was not statistically significant in these six studies. Therefore, a meta-analysis was carried out to evaluate the association of the IL-6-174 G/C polymorphism with discoid skin lesions and renal disease.…”
Section: Resultsmentioning
confidence: 78%
“…Four studies describe the association between this polymorphism and discoid skin lesions or renal disease. 13,19,21,23 However, the Schotte study did not provide the number of genotype distributions of patients negative for the features. 19 The Asano study only provided the genotype data under a recessive model.…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 is another multifunctional B-cell differentiation cytokine, which also plays important role in inducing the final maturation of activated B cells into immunoglobulin-secreting plasma cells and influencing the susceptibility of RA [ 7 , 8 , 11 , 22 – 24 ], dermatomyositis and systemic lupus erythematosus [ 39 ], liver cirrhosis and hepatocellular carcinoma [ 40 ], diabetic microvascular complications [ 41 ], coronary heart disease [ 42 ], acute appendicitis [ 43 ], and so on. Although the association of IL-6-174 G/C with RA was well studied in many populations, such as Europeans, Turkish, Koreans, and Egyptians, besides a very preliminary study in a few Han population in Guangdong, studies about the association of IL-6-174 G/C with RA in Chinese population do not be reported.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 (-174 C/G) is involved in the pathogenesis of some autoimmune disorders. Hristova et al [ 6 ] reported a statistically significant association between IL-6 -174G allele and systemic lupus erythematosus in Bulgarian population.…”
Section: Introductionmentioning
confidence: 99%